Initial Examination of the Trends in Speech Communication Theses, 1976 to 2015 - de Pano, Jose Carlo Garcia (Philippine Humanities Review; Vol 21 No 2 (2019), 2021)
This paper presents a preliminary analysis of speech communication theses submitted to the University of the Philippines Diliman Department of Speech Communication and Theatre (UPD DSCTA) Arts from 1976 to 2015. Findings revealed that those written between 1976 and 1985 mostly centered on the general components of human communication, whereas those completed from 1986 to 1995 were more particular to certain levels and areas of speech communication. The move from general to specific subjects of inquiry was maintained in the studies that were conducted from 1996 to 2005 and from 2006 to 2015. During these periods, most of the theses focused on more precise issues related to the different branches of speech communication. Results also showed interesting patterns of methods employed in the studies completed during the four decades covered in the analysis. From 1976 to 1985, students were more inclined to use quantitative techniques to address their research objectives. However, from 1986 to 1995 and from 1996 to 2005, an increasing number of studies evidently favored qualitative designs and rhetorical analyses. Finally, from 2006 to 2015, there was a return to postpositivist methods. The implications of these findings on the UPD DSCTA’s speech communication program structure and course offerings are discussed.